2017
DOI: 10.12657/denbio.078.005
|View full text |Cite
|
Sign up to set email alerts
|

Taxonomic differentiation of Salix retusa agg. (Salicaceae) based on leaf characteristics

Abstract: The complex of Salix retusa includes S. retusa s.s., S serpyllifolia and S. kitaibeliana, small, prostrate willows occurring in the subalpine and alpine vegetation belts of the mountains of Central Europe: the Pyrenees, Alps, Apennines, Dynaric Alps, Carpathians and Rila. The systematic positions of these taxa are not fully resolved and are still disputed. The aim of the present study was to biometrically verify differences in leaf characteristics between these taxa. Material was collected from 47 populations,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 9 publications
1
12
0
Order By: Relevance
“…A recent study on leaf morphology in S. retusa agg. (Kosiński et al 2017) confirmed that S. retusa s.l. populations in the Tatra Mountains (the western Carpathians) had leaf length and width twice as long as the average found for the rest of the populations of S. retusa s.l., which corresponds to the description of S. kitaibeliana, and justify from a morphological standpoint distinguishing them as a separate taxon.…”
Section: Introductionsupporting
confidence: 56%
See 4 more Smart Citations
“…A recent study on leaf morphology in S. retusa agg. (Kosiński et al 2017) confirmed that S. retusa s.l. populations in the Tatra Mountains (the western Carpathians) had leaf length and width twice as long as the average found for the rest of the populations of S. retusa s.l., which corresponds to the description of S. kitaibeliana, and justify from a morphological standpoint distinguishing them as a separate taxon.…”
Section: Introductionsupporting
confidence: 56%
“…In the Pyrenees, the connection between ploidy and leaf size was clearer and in line with expectations: lower ploidy (DNA hexaploidy) corresponds in these populations to smaller leaf sizes as compared to other populations of S. retusa s.s. (Kosiński et al 2017) (Fig. 2).…”
Section: Comparison With Earlier Studies Based On Chromosome Countingmentioning
confidence: 97%
See 3 more Smart Citations